AKTIVITAS DAN ISOLASI SENYAWA AKTIF PENGHAMBAT ENZIM ALFA-GLUKOSIDASE DARI EKSTRAK ETIL ASETAT DAUN STEVIA (Stevia rebaudiana Bertoni) SECARA IN VITRO - Laura Stephanie Joner; Lilik Sulastri; Partomuan Simanjuntak (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Stevia leaves (Stevia rebaudiana Bertoni) is a plant that commonly used as a natural sweetener to replace sugar. According to research, stevia has many health benefits and one of them is antidiabetic. The aims of this research are to determine the activity of the ethyl acetate extract of stevia leaves (Stevia rebaudiana Bertoni) as an inhibitor of -glucosidase enzyme. The stages on this research include extraction with 96% ethanol solvent, then the ethanolic extract was partitioned with ethyl acetate – water = 1:1. Isolation and purification of the ethyl acetate extract was carried out by column chromatography (SiO2; i). n-hexane – etil acetate = 10 : 1 1 : 1 ii). n-hexane – etil acetate = 20:1 which was guided by testing the inhibitory activity of α-glucosidase enzyme by in vitro studies. The results showed that the STEA-1.1 fraction had the best activity with IC50 value 39,55 ± 0,51 ppm compared to the partitioned ethyl acetate extract with an IC50 value 43,47 ± 0,05 ppm, while the acarbose had an IC50 value 19,24 ± 0,03 ppm. Keywords: Stevia rebaudiana Bertoni, α-glucosidase, Antidiabetic, Indonesian Medicinal Plants, IC50